Legal Research Concerning the Legal Status of Surat-Ijo Land Owned by the City Government of Surabaya - Sosilo, Peter (PT. Riset Press International, 2023)
The emergence of the liberation movement for the residents of the Surat-Ijo land is a form of response to the phenomenon of injustice that has surrounded and shackled some of the people of the city of Surabaya which has been going on for a long time. The emergence of the liberation movement was encouraged and facilitated by a situation that upheld the spirit of openness and freedom of expression, namely the spirit of reform that arose in the post-New Order era. One (of the many) factors that gave rise to the liberation movement for the residents of Surat-Ijo land is the difference in understanding of the applicable laws and regulations, especially the regional land laws and regulations. This difference in views has led to different perceptions between the two parties regarding the status of state land rights that are occupied by residents. The form of conflict resolution regarding the Surat-Ijo land can occur when there is a unified understanding between the residents of the Surat-Ijo land and the City Government of Surabaya regarding land laws and regulations, both national and local. Efforts to resolve the conflict require a bold breakthrough, not just to be handled legally which only involves the two parties to the dispute, but requires the involvement of at least three ministries, namely the Ministry of Home Affairs, the Ministry of Agrarian Affairs and Spatial Planning, and the Ministry of Finance. The settlement of the Surat-Ijo land conflict must be encouraged by the spirit of upholding justice and prosperity for all Indonesian people as the goal of the proclaimed Unitary State of the Republic of Indonesia (NKRI) in 1945.